TECHNIQUES OF PURIFICATION of ANTIGEN O ISOLATES of Escherichia coli AND IN VIVO ANALYSIS OF ANTIGEN IMMUNOGENICITY IN POULTRY - Achmad Bahtiar Rifai; Anita Yuni Praptiwi; Dwi Sulistiyono; Titis Wulandari (BIOEDUKASI, 2023)
Lipopolysaccharide (LPS) is a major surface component of most Gram-negative bacteria and is recognized by immune cells as pathogen-associated molecules. Antibodies against O antigens can provide protection against infection and vaccines have been developed by conjugating O antigens to carrier proteins to enhance immunogenicity. This study aims to produce O antigen from Escherichia coli and analyze the in vivo test results in poultry using ELISA technique. The methods used in this study were E. coli Bacterial Culture, O Antigen Purification, SDS PAGE, Inoculation on Experimental Animals, Rapid Plate Agglutination Test, and ELISA. Based on the results of the research conducted, it can be concluded that the O antigen of Escherichia coli injected into chickens can induce the formation of specific antibodies against E. coli in the blood. Specific antibodies to E. coli formed can be detected using the rapid plate agglutination test and ELISA technique.